Comparison of Efficient Ways of Mud Cake Removal from Casing Surface with Traditional and New Agents - Marcin Kremieniewski; Rafał Wiśniowski; Stanisław Stryczek; Paweł Łopata (Energies, 2021)
The tightness of the casing-rock formation interface is one of the most important elements of drilling and cementing jobs. In the absence of the required tightness, there is a risk of gas migration directly to the ground, groundwater or atmosphere. In order to eliminate this type of uncontrollable and unfavorable gas flows, the casing column is sealed with cement slurry in the annular space or beyond casing. Cement slurry displaces mud present in the annular space, although the mud cake cannot be completely removed, which is required for obtaining proper binding of cement slurry with the casing surface and the surface of the drilled formation. Therefore, it is important to prepare the well and remove the mud cake from the annular space with spacer fluid. An occasional lack of wellbore tightness requires continuous improvement of the cementing technology. Accordingly, analyses are conducted on mud cake removal with modified or new spacer fluids. Properly designed fluid should efficiently clean the surface of the casing and of the rock mass. One of the basic measurements is the analysis of the efficiency of mud cake removal from the surface of a rotational viscometer. The efficiency of traditional and newly designed fluids for mud cake removal from the casing surface with new and traditional agents has been compared further in this paper. The methodology of mud cake removal with the use of a rotational viscometer was also presented. Tests were performed for various concentrations of agents already used for spacer fluids and for a group of new agents. The efficiency of annular space cleaning was determined on the basis of a comparison with the results obtained for the reference sample, i.e., water which was used for mud cake removal from the rotor surface. The analysis of the results of experiments created bases for the comparison of the efficiency of the analyzed spacer fluids and finding the most suitable ones for mud cake removal from casing columns.